Engineering of Asymmetric Dual-Atom Sites for Effective Oxygen Electrocatalysis - Xue, Dongping; Zhao, Yu; Cao, Jianliang; Wang, Yan (Nano-Micro Letters, 2026)
Asymmetric dual-atom site catalysts (ADASCs) inherit the high atomic utilization of single-atom site catalysts and synergistic effects of symmetric dual-atom site catalysts, while uniquely integrating the asymmetry of heteronuclear metal centers and asymmetric coordination environments. This structural merit endows them with tunable electronic configurations and optimized reaction kinetics, breaking conventional catalysts’ inherent limitations to boost catalytic performance significantly. Despite existing reviews on dual-atom site catalysts for electrocatalysis, a comprehensive asymmetry-focused framework to elucidate ADASCs’ catalytic behaviors remains elusive. This review summarizes the multi-dimensional regulation mechanisms of ADASCs. Structurally, heteronuclear metal synergy and bridging ligand co-anchoring suppress single-atom agglomeration. Electronically, d-band center modulation, spin coupling, and orbital hybridization optimize intermediate adsorption energies. Subsequently, the strategies for constructing asymmetric structures are elaborated, including the design of heteronuclear metal centers and the regulation of asymmetric coordination environments via nonmetallic atom engineering. Furthermore, the prominent advantages of ADASCs in oxygen electrocatalysis are highlighted as their asymmetric configurations can break the linear scaling relationship of intermediate adsorption, and optimize the reaction pathway as well as the adsorption behaviors of key intermediates. Finally, the current challenges and opportunities of ADASCs are discussed, providing valuable insights for the development of high-performance energy conversion devices. Highlights: 1 The multi-dimensional performance optimization mechanisms of asymmetric dual-atom site catalysts (ADASCs) are summarized, laying a fundamental framework for understanding their catalytic behaviors. 2 Various strategies for constructing ADASCs are elaborated, with a focus on heteronuclear metal centers and heteroatom doping engineering to disrupt the symmetry between electric fields and structures. 3 The applications of ADASCs in oxygen electrocatalysis are systematically summarized, and the structure–performance relationship between asymmetric dual-site configurations and catalytic reactions is revealed.